Dual solutions of forced convection flow along a stretching sheet with variable thickness in presence of free stream and magnetic field - Upendra Mishra,; Gurminder Singh, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The paper aims at studying forced convection in a viscous incompressible electrically conducting fluid along stretching sheet with variable thickness in the presence of variable free stream and magnetic field. The governing equations of flow and heat transfer are subjected to similarity transformation using boundary layer assumption and are then solved numerically. The system of equations possesses dual solutions for negative value of velocity power index (m). The impact of velocity parameter (λ) and other parameters on velocity and temperature distributions, skin friction and heat transfer are studied when system possesses dual solutions and is presented through graphs and discussed suitably. It is found that the first solution is in tune with natural physical phenomena. The second solution possesses very large skin-friction and fluid velocity as compared to the first solution. The second solution is stable and is a mere outcome of non-linearity and does not follow natural phenomena.